Penggunaan Metode Eksperimen Dengan Pembelajaran Kooperatif Untuk Meningkatkan Minat Dan Hasil Belajar Pada Pokok Bahasan Peluang Di Kelas XI. IPA 2 SMAN 5 Muaro Jambi - Agustarizal (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract Most of the student difficulties in learning mathbecause this subject demands students for logical thinking andunderstanding the concepts relate numbers and imajiner. Thisstudy intends to improve students understanding of math conceptsin opportunity topic in order to increase students‟ learningachievement, and to create a fun learning in math.This study employs the classroom action research in twocycles in IPA X2 in SMAN 5 Muaro Jambi. This study found that:1) the student results learning is increasing, 2) students areactively in learning and highly participate in lerning